Gambling Problems in First Nations and Inuit Communities of Québec: A Brief Status Report - Papineau. Élisabeth (Institut national de santé publique du Québec, 2010)
Reproductions for private study or research purposes are authorized by virtue of Article 29 of the Copyright Act. Any other use must be authorized by the Government of Québec, which holds the exclusive intellectual property rights for this document. Authorization may be obtained by submitting a request to the central clearing house of the Service de la gestion des droits d’auteur of Les Publications du Québec, using the online form at http://www.droitauteur.gouv.qc.ca/en/autorisation.php or by sending an e-mail to droit.auteur@cspq.gouv.qc.ca. This report presents an overview of the data on gambling habits and problems in First Nations and Inuit communities of Québec. We will look at international research data on gambling and aboriginal populations, explore gambling opportunities available to First Nations and Inuit communities of Québec, and lastly examine prevalence data specific to Québec. Yes This study was commissioned by the Ministère de la Santé et des Services sociaux.